The Effectiveness of Tuina Massage in Overcoming Feeding Difficulties in Toddlers Aged 1-2 Years at Posyandu Mekar in the Talaga Village Area - Azizah Laksono, Nur; Nursitiyaroh, Nursitiyaroh (International Journal of Health and Pharmaceutical (IJHP), 2023)
Background : Toddlers are still completely dependent on their parents to perform the necessary tasks such as bathing, urinating, and eating. Purpose of Writing: to determine the effectiveness of tuina massage in overcoming eating difficulties in toddlers aged 1-2 years at TPMB X Talaga Village Region in 2022. Research Methods: This research was an experimental study designed with One – group pre test – post test design. The number of samples in this study were 40 people. The sampling technique was used by accidental sampling. Research Results: Statistical tests using the non-parametric Wilcoxon test obtained the result that the majority of 40 respondents were in positive ranks or the (positive) difference between before and after the Tuina Massage was carried out with the mean ranks being 20.50 and the sum of ranks being 820.00. Asymp research results. Given Sig (2 - Talled) = 0.001 and 0.000 <0.05, the hypothesis can be considered accepted. This shows that the Mekar Posyandu in the Talaga Village area has been successful in using Tuina Massage to help toddlers aged 1-2 years overcome the challenges of eating at the Mekar Posyandu in the Talaga Village Area. Conclusions and Suggestions: it is hoped that the parents of their children can find out a lot about their involvement in doing tuini massage as a form of alternative medicine so that mothers can do the Tuina Massage technique to overcome the problem of difficulty eating in toddlers 1-2 years.